TRENDS AND INNOVATIONS IN WORKFORCE MANAGEMENT - Yanuar Kirana, Angelika; Septiana, Sela; Ismail, Iriani (Universitas Islam Lamongan, 2024)
This article discusses trends and innovations in workforce management in the digital era, focusing on companies’ adaptation to technological changes and labor market dynamics. Human resource management (HRM) is undergoing significant transformation through the adoption of digital technologies such as artificial intelligence (AI) and human resource information systems, which facilitate the recruitment, training, and performance appraisal processes of employees. In addition, flexible working trends, such as remote working and hybrid working models, are gaining popularity, especially after the global pandemic. The article also examines the importance of employee well-being and satisfaction, which can be achieved through innovations in continuous training programs, digital health technologies, and inclusive work policies. This study uses a Systematic Literature Review (SLR) approach to identify current trends and innovations in workforce management, and formulate strategies that companies can implement to improve the performance and loyalty of their workforce in the future.